Extracorporeal shock wave lithotripsy of pancreatic stones. Issue 10 (October 1989) - Sauerbruch, T; Holl, J; Sackmann, M; Paumgartner, G
Abstract : Extracorporeal shock wave lithotripsy of pancreatic stones was performed in eight patients with chronic pancreatitis and a dilated duct system harbouring stones 5 to 20 mm (means 10 (SD) 5 mm) in diameter. After endoscopic sphincterotomy of the pancreatic orifice the stones were disintegrated by shock waves under fluoroscopic control using a kidney lithotripter (Dornier HM3). The procedure was well tolerated by all but one patient, who had a mild pancreatitic attack immediately after lithotripsy. Clearance of the pancreatic duct systems from the larger stones was achieved in seven of eight patients. Half of the patients showed no improvement in the intensity and frequency of pain. The other patients had a marked amelioration of symptoms, however, both immediately and during a mean follow up interval of 11 (eight) months. A selective combined approach by endoscopy and extracorporeal shock wave lithotripsy for the treatment of pancreatic stones seems promising.